Appraising the Community of Practice at a Hospital Library System Using a Critical Librarianship Lens. Issue 3 (2nd July 2020) - Rodriguez, Joy; Kanungo, Chandrika; Macias, Ana
Abstract: The Kaiser Permanente health sciences librarians created inter-regional policies to standardize and guide the work of all librarians across regions. In response to the larger organization's emphasis on promoting diversity and equity in healthcare and the workplace, the library policies have evolved over time to include aspects of critical librarianship in the information services that the Kaiser Permanente librarians provide to their organization. The article describes how the inter-regional group of hospital librarians provide information services through a critical librarianship lens and provides examples of how other health sciences librarians can incorporate these principles to expand their services.